The Mediating Role of Psychological Need Thwarting in the Relationship Between Compulsory Citizenship Behavior and Psychological Withdrawal - Bashir, Mohsin; Shaheen, Kanwal; Saleem, Sharjeel; Bhutta, Mohammed Khurrum; Abrar, Muhammad; Jun, Zhao (Frontiers in Psychology, 2019)
This study aims to test a novel process underlying the relationship between compulsory citizenship behavior and psychological withdrawal. Specifically, based on basic psychological needs theory, thwarting of autonomy and relatedness needs were expected to explain the association between compulsory citizenship behavior and psychological withdrawal. The PROCESS macro was used to analyze the data collected from 368 clerical staff working in public universities in Pakistan. The results confirmed that thwarting of autonomy and relatedness need mediated the relationship between compulsory citizenship behavior and psychological withdrawal. This study makes a significant contribution to the unexplored domain of the process employees use to cope with compulsory citizenship behavior. It also highlights the role of an understudied construct, i.e., psychological need thwarting as a crucial motivational mechanism for elucidating the relationship between compulsory citizenship behavior and psychological withdrawal. The findings of this study provide recommendations for future researchers, along with its implications for practitioners.